The effect of regulatory governance system on investment growth in decentralized Indonesia - Yuwono, Teguh; Wiryawan, Bangkit A.; Yuzuru, Shimada (Frontiers in Political Science, 2025)
This paper contributes to the ongoing debate on the relationship between governance systems and development by focusing on foreign direct investment (FDI) at the sub-national level in Indonesia. Following the implementation of political decentralization in 2005, provincial and district governments gained greater authority in drafting local regulations. The number of local bylaws increased significantly, especially after the introduction of the Local Tax Law in late 2009. However, the lack of a robust governance framework in the formulation of these regulations raised concerns at the national level. In response, the central government attempted to revoke numerous local laws, citing their adverse impact on the investment climate. As the proxy for governance quality, we used the number of problematic local regulations at the province level. Using a difference-in-difference estimation for the period 2005 to 2017, we found that provinces with weaker governance systems experienced a long-term decline in FDI growth of approximately 26–30% compared to the control group. Our event-study estimator confirmed that this negative trend persisted following the enactment of the local tax law. Further analysis revealed that the impact of governance on FDI is more pronounced in non-Java provinces and less severe in provinces with fewer natural resources. By considering provinces’ level of development and endowment, these findings suggest that poor governance practices and limited public participation in local decision-making are key factors undermining FDI performance.